Summary of a workshop on preclinical and translational safety assessment of CD3 bispecifics. Issue 1 (1st January 2020) - Kamperschroer, Cris; Shenton, Jacintha; Lebrec, Hervé; Leighton, John K.; Moore, Paul A.; Thomas, Oliver
Abstract: Currently, there is a multitude of CD3 bispecifics with different molecular designs and binding properties in preclinical and clinical development for the treatment of liquid or solid tumors. The key safety concerns with CD3 bispecifics are excessive release of cytokines, which may translate to potentially life-threating cytokine release syndrome (CRS), target organ toxicity due to redirection of T-cells to normal tissues expressing the tumor-associated antigen (TAA) (off-tumor/on-target cytotoxicity), and, in some instances, neurotoxicity. Another key challenge is to arrive at a safe clinical starting dose and an efficient escalating strategy that allows patients in early dose cohorts the potential for clinical benefit in Phase 1 trials. To expand the therapeutic index and bring more treatment options to patients, there are intense efforts to overcome these challenges through improvements in molecular design, preclinical safety assessment strategies, and clinical management practices. A recent workshop at the U.S. Food and Drug Administration (FDA) with industry, academic, and regulatory agency representation was held to discuss the challenges and explore where such improvements to the development of CD3 bispecifics can be implemented. Here, the content of the presentations and the discussion that occurred during this workshop are summarized.